Surgical accuracy of three-dimensional virtual planning: a pilot study of bimaxillary orthognathic procedures including maxillary segmentation. Issue 1 (January 2016) - Stokbro, K.; Aagaard, E.; Torkov, P.; Bell, R.B.; Thygesen, T.
Abstract: This retrospective study evaluated the precision and positional accuracy of different orthognathic procedures following virtual surgical planning in 30 patients. To date, no studies of three-dimensional virtual surgical planning have evaluated the influence of segmentation on positional accuracy and transverse expansion. Furthermore, only a few have evaluated the precision and accuracy of genioplasty in placement of the chin segment. The virtual surgical plan was compared with the postsurgical outcome by using three linear and three rotational measurements. The influence of maxillary segmentation was analyzed in both superior and inferior maxillary repositioning. In addition, transverse surgical expansion was compared with the postsurgical expansion obtained. An overall, high degree of linear accuracy between planned and postsurgical outcomes was found, but with a large standard deviation. Rotational difference showed an increase in pitch, mainly affecting the maxilla. Segmentation had no significant influence on maxillary placement. However, a posterior movement was observed in inferior maxillary repositioning. A lack of transverse expansion was observed in the segmented maxilla independent of the degree of expansion.